IMPLEMENTASI PERATURAN KEPALA BADAN PERTANAHAN NASIONAL NOMOR 3 TAHUN 2011 TENTANG PENGELOLAAN, PENGKAJIAN, PENANGANAN KASUS PERTANAHAN DI KOTA PROBOLINGGO - Wasilatur Rohima; Imam Sucahyo; Ach. Noor Busthomi (Public Service and Governance Journal, 2023)
Indonesian is an agricultural country, so land has a very important meaning for the life of the Indonesian people. So important is the position of land for humans, it often causes disputes about land. Theoretically, dispute resolution can be carried out in 2 (two) ways, namely through formal justice mechanisms in court (litigation) and outside the judicial process (non-litigation). One form of settlement outside the court is Mediation. Mediation is a dispute settlement through negotiation with the help of a neutral third party (mediator) to find a form of settlement that can be agreed upon by the parties. Mediation is basically deliberation and consensus, namely as a method or process other than other methods or processes, whether through arbitration, negotiation, conciliation, and others. If in mediation there is an agreement, and it is stated in a deed of peace, in fact this deed of peace is a legal product and has binding power as is characteristic of the consensual principle according to Article 1338 of the Indonesian Civil Code. Thus, an agreement made legally applies as a law for the parties to the dispute. This article uses a socio legal approach in a descriptive analytical manner through qualitative methods